Carrying Capacity Study of Coastal Tourism in Kumarakom, Kerala. - Syamlal G.S. Syamlal G.S. (Universitas Gunadarma, 2011)
Kumarakom Panchayath falls under Kottayam taluk and the Pallom developmentblock of the Kottayam district. At present 61.22 Hectare of land is categorized asResort area. Due to rapid growth of tourism, there will be a higher demand for landwhich will result in the faster development of the remaining resorts. It is assumed thatover and above 61.22 ha of already committed resort areas an additional 40.44 ha ofperennial crop with settlement will also be utilized for resort development and relatedactivities. For Kumarakom panchayath a future scenario (Year 2011) of spatialstructure has been worked out here based on the existing scenario and the envisagedchanges in the land use structure. In addition to the projected population of 27,300,the tourist equivalent population also has to be considered for evaluating all centralfacilities requirement as well as utilities service requirement for Kumarakompanchayath. This means Kumarakom Panchayath is loaded with 42,000 (27,300 +14,700) population instead of 27,300 natural population for providing services andfacilities. The holding capacity of 91.5 ha of resort area in Kumarakom Panchayathestimated till 2011 will be 3660 beds (40 x 91.5 beds). The holding capacity of touristbeds in Aymanam and Arpookara panchayaths will be 20% of 3660 i.e. 732 beds.Thus, total holding capacity will be approximately 4392 beds. Usual tourist staff ratioof a luxury resort of three to five stars is 1:3. Therefore, population equivalent for atourist is assumed as 4. This means for a holding capacity 3660 tourist in Kumarakompanchayaths, population equivalent of tourist will be 14, 640 (3660 x 4). Varioussuggestions regarding restricted development and environmental protection aresuggested through this study.